The commodification of life in "Y vendimos la lluvia", by Carmen Naranjo - Robles Murillo, Keylor (2021)
In this article the process of commodification of life is analyzed based on the story “Y vendimos la lluvia”, (1989) from the Costa Rican writer Carmen Naranjo. For the purposes of the theoretical approach, the premises of the sociocritical are taken as a basis and, in turn, the contributions of Marxist theories are integrated to study the process of neoliberalization and capitalization of all aspects of society. In the same way, it exposes the way in which capitalism is linked to two systems of domination: sexism-patriarchy and xenophobia. Finally, the use of the discursive strategy of irony by the author to challenge and question the values that govern the society where the narrated events take place is addressed.